2015
DOI: 10.1590/01000683rbcs20140732
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Soil Load-Bearing Capacity as a Function of Soil Mechanical Resistance to Penetration

Abstract: estimation of soil load-bearing capacity from mathematical models that relate preconsolidation pressure (σp) to mechanical resistance to penetration (PR) and gravimetric soil water content (U) is important for defining strategies to prevent compaction of agricultural soils. Our objective was therefore to model the σp and compression index (CI) according to the PR (with an impact penetrometer in the field and a static penetrometer inserted at a constant rate in the laboratory) and U in a Rhodic Eutrudox. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…One pass with the tractor was sufficient to match the soil bulk density values in the minimum tillage system with those found in the no-tillage system. This indicates that soil chiselling increases the soil susceptibility to compaction by agricultural traffic (Ortigara et al, 2015), and that, under these soil conditions and soil tillage systems, the effects of soil bulk density reduction by the chiselling operation are eliminated by the first tractor pass. This increase of soil bulk density values shows that agricultural traffic in chiselled soil can be detrimental to the soil structure (Moraes et al, 2013), instantly returning the soil to its compaction condition prior to chiselling (Moraes et al, 2016b).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One pass with the tractor was sufficient to match the soil bulk density values in the minimum tillage system with those found in the no-tillage system. This indicates that soil chiselling increases the soil susceptibility to compaction by agricultural traffic (Ortigara et al, 2015), and that, under these soil conditions and soil tillage systems, the effects of soil bulk density reduction by the chiselling operation are eliminated by the first tractor pass. This increase of soil bulk density values shows that agricultural traffic in chiselled soil can be detrimental to the soil structure (Moraes et al, 2013), instantly returning the soil to its compaction condition prior to chiselling (Moraes et al, 2016b).…”
Section: Resultsmentioning
confidence: 97%
“…Tension transmission through the soil profile depends on factors related to the axle load of the equipment (Lamandé & Schjønning, 2011a), the tire-ground contact pressure , and on the number of machine passes (Moraes et al, 2013). In addition, the intensity of agricultural traffic-induced soil compaction is dependent on the degree of compaction (Moraes et al, 2013), water content (Lamandé & Schjønning, 2011b), and mainly on the soil structure (Hamza & Anderson, 2005) due to the lower stability of the connections between aggregates (Moraes et al, 2017), observed in the plots with chiselled soil, which indicates a lowerload support for machine traffic (Ortigara et al, 2015). Tillage systems and traffic levels interactions in the soil layers indicate that the penetration resistance values were altered by the traffic of the tractor, in different ways, in the soil profile due to soil preparation ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms involved in the age-hardening phenomena have been related to the rearrangement of soil particles via flocculation of clay particles accompanied by changes in pore size distribution and restoration of cementing bonds between soil particles, reflecting increase in tensile strength (Tormena et al, 2008). Soil load support capacity is an important parameter for soil physical quality, directly related to soil structure (Ortigara et al, 2015) and the condition to root growth (Keller et al, 2015). This parameter is related to aggregate-tensile strength (Mosaddeghi et al, 2003), thus the age-hardening phenomenon (Moraes et al, 2017;Utomo and Dexter, 1981) could be evaluated by soil load support capacity to analyse the strengthening of soil structure.…”
Section: Tablementioning
confidence: 99%
“…Most soil properties associated with σ p and hence, with soil load support capacity, are influenced by cropping and soil tillage systems (Moraes et al, 2017;Ortigara et al, 2015;Pires et al, 2017).…”
Section: Introductionmentioning
confidence: 99%